Friendship : a how-to guide - Burns, Jan. (Berkeley Heights, NJ : Enslow Publishers, 2012)
A guide for teen girls, explaining ways to forge and maintain lasting friendships.
Includes bibliographical references and index.
Booklist
Booklist, January 2012
Young Adult.
Young Adult
Keywords: Friendship -- Juvenile literature; Friendship; Friendship